2016
DOI: 10.1002/jhet.2756
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design to Construct Pyridinonethiol and Its Annulated Frameworks of Expected Significant Antitumor Activity and Geometrical Optimizations

Abstract: We exploited the utilization of 2‐methyl‐2‐phenyl‐1,3‐oxathiolan‐5‐one (1) that acts as activated thioglycolic acid as mercaptoacetyl transfer agent to build new pyridinonethiol derivatives via multicomponent domino reactions of 1 with different acyclic or cyclic α,β‐unsaturated carbonyl compounds and aniline using CeCl3∙7H2O/KI as Lewis acid catalyst. Furthermore, the new synthesized compounds were biologically evaluated for antitumor efficiency. The geometries and normal modes of vibrations obtained from cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Gaussian 09 program package was used to evaluate the cluster calculation [20] via using (B3LYP) exchange functional in the presence of density functional theory (DFT) level with a combination of 6‐311G(d to p) as basis set were used to perform density functional theory (DFT) of synthesized compounds. In addition, the quantum chemical calculations (the energies of the HOMO and LUMO) have been revealed that frontiers orbitals (E HOMO ‐E LUMO ) energy gap is an important stability index, and impacts the biological activities of the molecules [21,22] . As a large energy gap indicates high stability for the molecule in chemical reactions and gives an indication of the weakness of its biological activity, these molecules called hard molecules.…”
Section: Molecular Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaussian 09 program package was used to evaluate the cluster calculation [20] via using (B3LYP) exchange functional in the presence of density functional theory (DFT) level with a combination of 6‐311G(d to p) as basis set were used to perform density functional theory (DFT) of synthesized compounds. In addition, the quantum chemical calculations (the energies of the HOMO and LUMO) have been revealed that frontiers orbitals (E HOMO ‐E LUMO ) energy gap is an important stability index, and impacts the biological activities of the molecules [21,22] . As a large energy gap indicates high stability for the molecule in chemical reactions and gives an indication of the weakness of its biological activity, these molecules called hard molecules.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…In addition, the quantum chemical calculations (the energies of the HOMO and LUMO) have been revealed that frontiers orbitals (E HOMO -E LUMO ) energy gap is an important stability index, and impacts the biological activities of the molecules. [21,22] As a large energy gap indicates high stability for the molecule in chemical reactions and gives an indication of the weakness of its biological activity, these molecules called hard molecules. On contrast, compounds with little gap are more polarized and called soft molecules.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The antioxidant screening of the investigated compounds was determined in vitro using the technique prescribed in literature . The inhibition for each derivative was calculated using the following mathematical equation.…”
Section: Biological Activitymentioning
confidence: 99%